Ala-ul Mulk: A Political Genius and Confidant of Alauddin Khalji (Indian Journal of Social Science and Literature (IJSSL), 2024)
Alauddin Khalji had usurped power with the help of his friends and confidants. Besides Ulugh Khan (brother of Alauddin Khalji), Zafar Khan Nusrat Khan and Alp Khan, he had Malik Ala-ulMulk a very trusted person, in his confidential circle. He was posted with Alauddin Khalji during his governorship of Kara. This officer of Alauddin misled Sultan Jalaluddin Khalji by his fabricated reports when Alauddin Khalji took a bold action of proceeding on an expedition to Devagiri without obtaining permission of the Sultan. From his Kara days till his death, Ala-ul Mulk remained a confidant of Alauddin Khalji and gave him his sincere advices whenever the Sultan asked for. He was an officer who always spoke fearlessly while giving his sincere advices even against the wishes of the Sultan. His sincerity and truthfulness was truly acknowledged by the Sultan.